A COMPARISON OF TOPICAL MENTHOL TO ICE ON PAIN, EVOKED TETANIC AND VOLUNTARY FORCE DURING DELAYED ONSET MUSCLE SORENESS - Johar, Pramod (Sports Physical Therapy Section, 2012)
PURPOSE/BACKGROUND: Pain can adversely affect muscle functioning by inhibiting muscle contractions. Delayed onset muscle soreness was used as a tool to ascertain whether a topical menthol-based analgesic or ice was more effective at reducing pain and permitting greater muscular voluntary and evoked force. METHODS: Sixteen subjects were randomized to receive either a topical gel containing 3.5% menthol or topical application of ice to the non-dominant elbow flexors two days following the performance of an exercise designed to induce muscle soreness. Two days later, DOMS discomfort was treated with a menthol based analgesic or ice. Maximum voluntary contractions and evoked tetanic contractions of the non-dominant elbow flexors were measured at baseline prior to inducing muscle soreness (T1), two days following inducing DOMS after 20 (T2), 25 (T3) and 35 (T4) minutes of either menthol gel or ice therapy. Pain perception using a 10-point visual analog scale was also measured at these four data collection points. Treatment analysis included a 2 way repeated measures ANOVA (2 × 4). RESULTS: Delayed onset muscle soreness decreased (p = 0.04) voluntary force 17.1% at T2 with no treatment effect. Tetanic force was 116.9% higher (p<0.05) with the topical analgesic than ice. Pain perception at T2 was significantly (p=0.02) less with the topical analgesic versus ice. CONCLUSIONS: Compared to ice, the topical menthol-based analgesic decreased perceived discomfort to a greater extent and permitted greater tetanic forces to be produced. LEVEL OF EVIDENCE: Level 2b